Kemampuan berpikir kreatif matematika siswa melalui pendekatan contextual teaching and learning - Ahmad, Marzuki; Rohani, Rohani (Mahesa Research Center, 2023)
This study aims to describe the improvement of students' Mathematical Creative Thinking Ability (MCTA) in learning mathematics with the Contextual Teaching and Learning (CTL) approach. So that the goals that have been set can be achieved, quasi-experimental research is carried out with the design of the Nonequivalent Control Group Design. The population of this research is the students of class X SMA Negeri 2 Padangsidimpuan. The research sample was taken using a purposive sampling technique, namely class X MIA 3 for the experimental group and MIA 4 for the control group. The research carried out showed that the results of the MCTA students through the Independent Samples Test obtained a significance level of 0.00 <0.05. This means that there is a significant average difference between the increase in the MCTA of the experimental group students and the control group. Furthermore, the average value of the N-gain score for the experimental group is 0.41 and the control group is 0.29. This means that the improvement of students' MCTA through the CTL approach is better than learning with the conventional approach. Furthermore, with two-way ANOVA analysis, obtained a significance level of 0.196> 0.05. This means that there is no interaction with initial abilities with the learning approach in improving students' MCTA.